Investigation of nanotexture fabrication by magnetic field assisted ultra-precision diamond cutting - Tao He; Muhammad Rehan; Linhe Sun; Jiuxing Tang; Denghui Li; Lulin Chen; Lingling Chen; Suet To; Wai Sze Yip (PLoS ONE, 2025)
Ultra-precision machining (UPM) is crucial for producing parts with functional surfaces featuring nano textures, yet it faces challenges in generating such textures. This paper explores the potential of magnetic field-assisted UPM to overcome these challenges by leveraging magnetophoresis to generate nanotextures and thoroughly investigating the importance of cutting velocity on magnetophoresis in diamond cutting. Experimental results from cutting force, surface profile, surface topography, and atomic force microscopy images demonstrate that magnetic fields enable nanotexture generation on aluminum alloys surfaces in diamond cutting. Also, increasing cutting speed in diamond cutting under a magnetic field enhances magnetophoresis. This study highlights the advantages of integrating magnetophoresis for advanced nanotexture fabrication in UPM and emphasizes strategies for control cutting speed to achieve nanotextures.